Rancang Bangun Aplikasi (Point of Sales) Berbasis Website Menggunakan Framework Laravel dengan Metode Menggunakan Prototype - Taufik, Imam; Ichwani, Arief (Majalah Ilmiah METHODA, 2024)
BO'Coffee is a business in the culinary sector where every day there are buying and selling transactions which of course record all types of sales transactions. The operational system used still uses manual methods which are considered vulnerable to errors in ordering and payment. This research uses the Laravel framework based on the prototype method. The aim is to increase operational efficiency through digitizing transaction processes and stock management. The prototype method was chosen because of its ability to develop iteratively and be responsive to user needs. The designed application offers convenience in managing transactions, monitoring inventory and real-time financial reporting. Test results show significant improvements in transaction time efficiency and data accuracy, supporting more effective decision making, the application functions well in all aspects tested, and all expected features can operate in accordance with the design and specifications that have been determined.